MODERNIZATION OF ORGANIZATIONAL AND ADMINISTRATIVE MECHANISM FOR STATE REGULATION OF LAND RELATIONS IN TERRITORIAL PLANNING AND DEVELOPMENT - Suvorov V.P. (Pressing Problems of Public Administration, 2015)
Based on the conducted research, the paper summarizes the guidelines and practicalmeasures aimed at improving an organizational and administrative mechanism for the stateregulation of land relations in the territorial planning and building of Ukraine.